Increasing Influenza Immunization Rates Among Retail Employees: An Evidence-Based Approach. (September 2017) - Montejo, Leigh; Richesson, Rachel; Padilla, B. Iris; Zychowicz, Michael E.; Hambley, Crystal
Influenza has a significant impact on the health of Americans and the U.S. economy. Annual influenza immunization can decrease the burden of influenza-related illnesses for both employees and employers. This project evaluated a nurse practitioner–led intervention to increase influenza immunization rates among retail employees from August through December of the 2015-2016 influenza season. The sample included employees from retail locations with on-site convenience care clinics staffed by nurse practitioners. This quality improvement project used a pre–post implementation evaluation design and compared influenza immunization rates of employees, before and after an intervention, at one worksite, and influenza immunization rates of employees, who did not receive the same intervention, at a comparison site. The intervention site employees were immunized at a higher rate than employees at the comparison site. Interventions, including health care professional–led education, program promotion, on-site access to and no-cost immunizations, choice of immunization delivery, and incentives, should be considered to increase immunization rates among employees.